ISOLASI DAN IDENTIFIKASI SENYAWA ANTIBAKTERI MINYAK ATSIRI DAUN KEMBANG BULAN Tithonia diversifolia (Hemsley) A. Gray - Hartati Soetjipto; Lusiawati Dewi; Sentot Adi Prayitno (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Isolation and identification of chemical compounds and antibacterial compounds of the essential oil of Kembang bulan or Japanese sunflower Tithonia diversifolia (Hemsley) A. Gray leaves showed that the essential oil contain 29 components. The main components were caryophyllene (27.76%), nerolidol (21.81%),caryophyllene oxide (7.06%), copaene (6.41%) and bicylogermacrene (4.90%). The oil was screened for their antibacterial activity through bioautography method. Two antibacterial spots which had Rf 0.49 and Rf 0.61were obtained. The spot with Rf 0.49 was a mixture of 21 compounds with main compounds were heneicosane, nonacosane and tetratetracontane, while the spot with Rf 0.61 consisted of 22 compounds, which the main compound was nerolidol.